Social Accounting as an Enabling Tool to Develop Collective Organizational Citizenship Behavior in the Diocese of Bilbao - Retolaza, Jose Luis; Aguado, Ricardo; San-Jose, Leire (Frontiers in Psychology, 2020)
Religious oriented organizations (ROOs) have frequently higher levels of motivation among their employees, due to the fact that the aims of ROOs and those of collaborators and stakeholders are usually aligned. However, when the management of ROOs become professionalized, tensions between aims and efficiency are more frequent, and productivity levels start to decline. In this research we will propose the use of social accounting to calculate the social value generated by ROOs and, from that point, build new indicators able to measure the organizational citizenship behavior (OCB) of collaborators working in ROOs. We will exemplify this theoretical development with the actual case of the diocese of Bilbao. As this case shows, managers in ROOs can increase organizational and individual OCB generating moral satisfaction for employees and collaborators in their organizations.